Outsourcing and Employer Responsibility: A Case Study of Occupational Health and Safety in the Danish Public Transport Sector - Hasle, Peter (Relations industrielles / Industrial Relations, 2007)
The widespread use of outsourcing in the service industry has major consequences for the employment relationship. In particular, outsourcing diminishes absolute employer control of firm operations. This article focuses on this new relationship through a study of the occupational health and safety requirements established in connection with the outsourcing of public bus transport in Denmark.